Scoliosis induced by costotransversectomy in minipigs model - Javier Cervera-Irimi; Álvaro González-Miranda; Óscar Riquelme-García; Jesus Burgos-Flores; Carlos Barrios-Pitarque; Pedro García-Barreno; Azucena García-Martín; Eduardo Hevia-Sierra; Giuseppe Rollo; Luigi Meccariello; Luigi Caruso; Michele Bisaccia (Medicinski glasnik, 2019)
Aim: To validate surgical costotransversectomy as a technique for creating a scoliosis model in minipigs and to assess whether differences in approach (posterior medial approach, posterior paramedial approach and anterior approach by video-assisted thoracoscopy) lead to differences in the production of spinal deformity. Creation of disease models in experimental animals, specifically in minipigs, is controversial, as no appropriate technique has been reported. Methods: Surgical costotransversectomy was performed in 11 minipigs using 3 different approaches: posterior medial approach (4 animals, group I), posterior paramedial approach (3 animals, group II) and anterior approach by videothoracoscopy (4 animals, group III). A conventional x-ray study was performed in the immediate postoperative period. Follow-up lasted for 4 months. Specimens were humanely killed according to current protocols, and a second x-ray study was performed. A deformation was measured using the Cobb angle and direct observation of the rotational component. Results: Data from group I revealed a scoliosis deformation of 27º-41º (mean 34.5º) with a macroscopic rotational component. No deformity (<10º) or rotational component was observed in groups II and III. Only a posterior medial costotransversectomy produced a significant deformity in minipigs and established a valid model for studying scoliosis in these animals. Conclusion: Only a posterior medial costotransversectomy produces a significant deformity in minipigs and establish a valid model for studying scoliosis in these animals. A tensegrity model would elucidate such results and harmonize disparate conclusions. Further investigation is needed to demonstrate the reliability of tensegrity principles for spinal biomechanics.
Keywords: experimental animal; model; spinal curvatures